PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA GAMBAR BERBASIS KOLASE PADA PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH PADANGSIDIMPUAN - Maulana Arafat Lubis (IAIN Padangsidimpuan, 2020)
The problem that is found in this research is low learning outcomes of IV grade student in MI Padangsidimpuan Angkola Julu in thematic learning. The problem is caused learning system given by teacher still not fun, so it does not make student desire in following the learning. This research is conducted to improve learning outcome of IV grade student in MI Padangsidimpuan Angkola Julu in following thematic learning in the theme the beauty of diversity in my country, material magnetic force and gravitational force using collage picture media. This is classroom action research that is consisted of two cycles and every cycle consist of four steps, they are (1) planning, (2) implementation, (3) observation, (4) reflection. The technique of data collection uses observation, test, and interview. Data analysis techniques are conducted qualitatively and quantitatively using questionnaire data analysis in the form of percentages (%) to get the success of image media implementation toward student’s learning outcome. Based on the results of teacher’s observations using collage picture media that it obtains 85,5% in the first cycle and 92,5% in the second cycle. The data shows an increase in teacher’s activity in improving student’s learning outcomes. Based on observation result, there is increase in student’s learning outcome where cycle I gets 60% and cycle II gets 84%. The average of student’s learning outcome gets increase percentage of 24%. Research result can be concluded that the use of collage picture media can improve student’s learning outcome on thematic learning.